Estimating Classroom Activeness in Science Learning: Proportions, Benchmarks, and Implications in an Indonesian Junior High - Nadia, Elga; Putri Yani, Vebbri; Elgrice, Vegita (Yayasan Darussalam Bengkulu, 2023)
This study addresses the need for classroom‐level evidence on student activeness in junior-high science by estimating the proportion of learners across engagement categories during routine lessons. Using a quantitative, descriptive, cross-sectional design, data were collected in a single administration from an intact eighth-grade class at SMPN 14 Bengkulu City (N = 30; 15 male, 15 female; response rate 100%). A 15-item Likert-type questionnaire operationalized five indicators of classroom activeness (participation in discussions, articulating opinions, initiating questions, problem solving, and involvement in practical work). Responses were summarized as frequencies and percentages across five categories (Inactive, Less active, Moderately active, Active, Very active). Results showed no students in the Inactive or Less active categories (0% each), with 10% Moderately active, 30% Active, and 60% Very active, indicating a strongly favorable engagement profile in day-to-day science instruction. These findings suggest that classroom routines in the observed setting support frequent student voice, questioning, and hands-on involvement, and they provide a category-based benchmark that makes heterogeneity visible for instructional decision-making. The principal contribution is a practical baseline reported as proportions rather than only mean scores that schools can use to set targets, tailor supports for moderately active students, and monitor shifts over time. Implications include guiding teacher professional development toward participation-eliciting routines, informing resource allocation for practical activities, and establishing a measurement approach that can be scaled and triangulated (e.g., with classroom observations) to drive continuous improvement in lower-secondary science learning.